1977
DOI: 10.1111/j.1365-2990.1977.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyneuropathies and CNS Protein Metabolism. I. Description of the Acrylamide Syndrome in Rats

Abstract: Behavioural, histological and metabolic studies were performed on acrylamide‐intoxicated rats. Treated rats showed disturbed food and water consumption accompanied by loss of body weight. In addition, in an open field test they displayed less ambulation and rearing activity than controls, and had severe difficulties in balancing on a rotating rod. The last test gives a reliable indication of the acryla‐mide‐induced disorder before the onset of histological changes. In the discussion it is suggested that the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…treated rats are polydipsic suggesting that a certain water inbalance may exist in these animals (Gipon et al, 1977;Squibb and Tilson, unpublished observation).…”
Section: The Effect Of Repeated Treatment With Aery/amidementioning
confidence: 94%
See 1 more Smart Citation
“…treated rats are polydipsic suggesting that a certain water inbalance may exist in these animals (Gipon et al, 1977;Squibb and Tilson, unpublished observation).…”
Section: The Effect Of Repeated Treatment With Aery/amidementioning
confidence: 94%
“…This chemical appears to damage nerve tissue selectively and has been known for some time to cause peripheral neuropathies (Fullerton and Barnes, 1966;Pleasure et al, 1970;Schaumberg et al, 1974). More recently central nervous system involvement in acrylamide poisoning has also been reported in experimental animals (Ghetti et al, 1973;Gipon et al, 1977;Schotman et al, 1978;Schaumburg and Spencer, 1978). Acrylamide poisoning leading to distinct 89 central nervous system behavioral deficits and encephalopathy has also been reported (Fujita et al, 1961;Igisu et al, 1975).…”
mentioning
confidence: 97%
“…It has been shown that rats treated with acrylamide either 20 mg/kg/day or 50 mg/kg/day showed a decrease in food intake and failed to grow normally (Gipon et al, 1977). Therefore, a pair-fed control group, injected with saline and fed the same amount of food as was consumed by the acrylamide-treated group the day before, was also investigated.…”
Section: Animals and Treatment With Acrylamidementioning
confidence: 99%
“…For this reason, a group of animals (group D) treated with a relatively high cumulative dose of acrylamide (450 mg/kg) was compared not only with saline-treated controls given food ad libitum, but at the same time with saline-treated controls pair-fed with the experimental animals (Table 1). (For details on food intake and body weight, see Gipon et al, 1977). The incorporation rates after injection of [3H]-leucine were determined as before.…”
Section: Tissue Uptake Of 3h-radioactivity and Incorporation Into Spimentioning
confidence: 99%
See 1 more Smart Citation